KEKUATAN LINGUAL PUISI-PUISI MASURI S.N - Pastika, I Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Abstract The strength of Masuri poems can be identified in various linguistic aspects that emerge the quality of the messages and the beauty of Malay language and literature. His works mostly exhibit the standard Malay that underline communicativeness, familiarity and solidarity. Masuri does not seem to like to manipulate language in terms of grammar and the lexical choice but his poems is not meant to be explicit. The sound parallelism, word choice and syntax constructions are really quite unique stylistic for Masuri works. To interpret the meaning or the message of his poems one should be ready with various knowledge such as Malay culture, Malay people and Singaporean politics.